2017
DOI: 10.5935/medicalexpress.2017.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Dental Neglect, one type of child abuse – Narrative review

Abstract: Dental neglect is defined as an intentional failure of the caretaker in the pursuit and continuity of necessary treatment to achieve an oral health that allows adequate function, free from pain and infection. We intend to clarify, according to the current scientific literature, the clinical indications for the identification of dental neglect in children. After the search in databases and search engines with the keywords "child", "dental" and "neglect", between 1996 and 2016, the results revealed that identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 20 publications
(57 reference statements)
0
7
0
9
Order By: Relevance
“…Exploring the relationship between dental neglect and other forms of maltreatment was a central theme of the included papers. By comparing children already affected by maltreatment with a general population sample, several papers found evidence that maltreated children had significantly poorer dental health than children in the general population (Baptista et al, 2017; da Silva-Júnior et al, 2018; Duda et al, 2017; Keene, Skelton, Day, Munyombwe & Balmer, 2015; Kvist, Malmberg, Boovist, Larheden & Dahllof, 2012; Lourenco, de Lima Saintrain & Gomes Fernandes Vieira, 2013; Valencia-Rojas, Lawrence & Goodman, 2008), although one study did not identify this association (Badger, 1986). Duda et al (2017), for example, found that maltreated children had a higher incidence of dental caries, missing primary teeth and untreated permanent decay.…”
Section: Resultsmentioning
confidence: 99%
“…Exploring the relationship between dental neglect and other forms of maltreatment was a central theme of the included papers. By comparing children already affected by maltreatment with a general population sample, several papers found evidence that maltreated children had significantly poorer dental health than children in the general population (Baptista et al, 2017; da Silva-Júnior et al, 2018; Duda et al, 2017; Keene, Skelton, Day, Munyombwe & Balmer, 2015; Kvist, Malmberg, Boovist, Larheden & Dahllof, 2012; Lourenco, de Lima Saintrain & Gomes Fernandes Vieira, 2013; Valencia-Rojas, Lawrence & Goodman, 2008), although one study did not identify this association (Badger, 1986). Duda et al (2017), for example, found that maltreated children had a higher incidence of dental caries, missing primary teeth and untreated permanent decay.…”
Section: Resultsmentioning
confidence: 99%
“…La CIT genera un impacto negativo en el estado de salud bucal y general del niño y afecta de forma significativa al entorno familiar ( [12][13][14]16,18,35,36 ), como se observó en los resultados de esta investigación, en la que el 70% (130 niños) presentaron lesiones de caries en diversos estadios según el sistema ICDAS II, siendo este valor mayor que lo reportado por Torres y cols. ( 11 ) sobre frecuencia de caries en niños provenientes de áreas urbano-marginales (62,3%).…”
Section: Discussionunclassified
“…En el presente estudio, se registraron signos clínicos sugerentes de negligencia en el cuidado dental y que si bien es cierto destacan la falla o la demora en la búsqueda de la atención odontológica por parte de las madres, no se puede considerar únicamente el registro del número de lesiones de caries dental presentes, sino también la presencia de enfermedad gingival, dolor o infecciones crónicas sin resolver, y el impacto significativo en el niño relacionado con otras características asociadas a los determinantes sociales de la familia y la evaluación psicosocial de la familia ( 22,35,36 ), las cuales no fueron analizadas con detenimiento en esta investigación por no formar parte de sus objetivos, pero que probablemente sí pudieron haber influido de manera negativa en el estado de salud del niño. Existen estudios en los que se menciona que los niños afectados por la dinámica de un hogar de condiciones sociales bajas donde coexisten problemas domésticos de negligencia, abuso o uso de sustancias o alcohol, presentaron altos niveles de caries, placa bacteriana, sangrado gingival y una falla en la continuidad de las citas y ausencia a las mismas en un periodo de dos años ( 22,36 ), en comparación con grupos controles.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A negligência bucal pode aparecer associada a vários sinais, como: dor orofacial crônica, trauma da região orofacial, cárie não tratada, atendimento odontológico inacabado apesar de os cuidadores serem informados da necessidade, infecções orofaciais repetidas e edema orofacial devido a abscessos dentais ou celulite (BAPTISTA et al, 2017).…”
Section: Negligênciaunclassified